1990
DOI: 10.2337/diab.39.7.802
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Pancreas Transplantation on Cardiorespiratory Reflexes, Nerve Conduction, and Mortality in Diabetes Mellitus

Abstract: Cardiorespiratory reflexes (CRR) were studied by measuring heart-rate variation during 6 breaths/min respiration and a Valsalva maneuver in 232 insulin-dependent diabetic subjects. Abnormalities were found in 175 patients. During a 7-yr follow-up, 41 (23.4%) patients with abnormal and 2 (3.5%) with normal CRR tests died. The mortality rates of diabetic patients with abnormal autonomic function tests were 17% at 2.5 yr, 33% at 5 yr, and 40% at 7 yr, significantly higher (P less than 0.002) than in patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0
2

Year Published

1994
1994
2015
2015

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 151 publications
(42 citation statements)
references
References 26 publications
2
38
0
2
Order By: Relevance
“…This is in contrast to all other standard measures of neuropathy, including detailed QST, autonomic function, electrophysiology, and IENFD, all of which failed to show an improvement 12 months after SPK. These findings support previous studies in diabetic neuropathy where at best a prevention of progression in nerve damage was shown only after several years of euglycemia (58,4851). However, these studies focused heavily on electrophysiology and quantitative sensory assessment, which predominantly assessed large fiber function.…”
Section: Discussionsupporting
confidence: 92%
“…This is in contrast to all other standard measures of neuropathy, including detailed QST, autonomic function, electrophysiology, and IENFD, all of which failed to show an improvement 12 months after SPK. These findings support previous studies in diabetic neuropathy where at best a prevention of progression in nerve damage was shown only after several years of euglycemia (58,4851). However, these studies focused heavily on electrophysiology and quantitative sensory assessment, which predominantly assessed large fiber function.…”
Section: Discussionsupporting
confidence: 92%
“…One major contributor to the diminished ventilatory responses in diabetic rats may be associated with development of autonomic neuropathy . Navarro and coworkers (19) documented abnormalities of cardiopulmonary reflexes in 75% of the 232 insulin-dependent diabetic patients. Many of these patients had evidence of somatic and autonomic 3a.…”
Section: Discussionmentioning
confidence: 97%
“…Studies performed on pancreas-transplanted patients have shown that diabetic glomerular lesions affecting their own kidneys prior to transplantation were not ameliorated by 5 years of normoglycaemia, while an improvement was observed after 10 years [12, 13] (Table 1). Different studies have shown that neuropathy progression (and the associated vascular degeneration) can be halted by successful pancreas transplantation [15, 25, 26]. Martinenghi et al reported that progressive amelioration of nerve conduction velocity was prominently related to the pancreas graft, given that in a cohort of kidney-pancreas-transplanted patients, the failure of the pancreas, that occurred at least 2 years after successful combined transplantation, was associated with a deterioration of nerve conduction velocity back to pretransplant levels [27].…”
Section: β-Cell Replacementmentioning
confidence: 99%